Effectiveness of food safety managerial training : face-to-face or computer-based delivery - Strohbehn, Catherine H.; Arendt, Susan W.; Ungku Zainal Abidin, Ungku Fatimah; Meyer, Janell (Foodservice Systems Management Education Council and The National Association of College & University Food Services, 2013)
Because cases of foodborne illnesses are es